Development of a Streaming Video Broadcast System About the Environmental Space of A Mobile Robot Based on ESP32-Cam - Yevsieiev, V. (Черкаського національного університету імені Богдана Хмельницького, 2023)
The development of a computer vision system for streaming video from a mobile robot based on the ESP32-Cam module.
Keywords: vision systems; mobile robots; ESP32-Cam